Teachers' Strategies for Addressing Learning Disabilities in Second-Grade Pancasila Education - Halimah, Siti Nur; Dianasari; Labudasari, Erna (Papanda Publisher, 2025)
Learning disabilities represent significant challenges in elementary education, with teachers playing crucial roles in identifying and addressing these difficulties. Understanding teachers' intervention strategies is essential for improving educational outcomes for students with learning disabilities, particularly in Indonesian elementary school contexts where research remains limited. This qualitative descriptive study was conducted at SDN 1 Keraton, involving 22 second-grade students and their homeroom teacher. Data collection utilized systematic classroom observations during Pancasila Education lessons on school rules and in-depth interviews with the teacher. Triangulation techniques ensured data validity, while inductive analysis identified learning disability patterns and teacher intervention strategies across educator, mentor, and assessor roles. The study revealed that 68.2% of students (15 out of 22) experienced learning disabilities, categorized into four types: material comprehension difficulties (54.5%), assignment completion challenges (45.5%), low classroom engagement (59.1%), and behavioral adaptation issues (36.4%). Teacher intervention strategies showed mixed effectiveness, with successful implementation of supportive classroom environments but limited provision of individualized guidance, emotional support, and competency-based assessments. The teacher demonstrated awareness of varied instructional approaches but struggled with systematic implementation, particularly in addressing social-emotional aspects of learning disabilities. The higher prevalence rate compared to international standards suggests contextual factors unique to this educational environment. While teachers employed multi-faceted approaches encompassing educator, mentor, and assessor roles, significant implementation gaps existed. The findings align with previous research emphasizing the importance of comprehensive support systems but highlight challenges in translating theoretical knowledge into consistent practice. These results contribute to understanding learning disability prevalence in Indonesian elementary contexts and reveal the complexity of teacher intervention strategies in resource-limited settings.